Whole-Genome DNA Methylation Dynamics of Sheep Preimplantation Embryo Investigated by Single-Cell DNA Methylome Sequencing - Zhang, Zijing; Xu, Jiawei; Lyu, Shijie; Xin, Xiaoling; Shi, Qiaoting; Huang, Yongzhen; Yu, Xiang; Zhu, Xiaoting; Li, Zhiming; Wang, Xianwei; Lang, Limin; Xu, Zhaoxue; et al. (Frontiers in Genetics, 2021)
The early stages of mammalian embryonic development involve the participation and cooperation of numerous complex processes, including nutritional, genetic, and epigenetic mechanisms. However, in embryos cultured in vitro, a developmental block occurs that affects embryo development and the efficiency of culture. Although the block period is reported to involve the transcriptional repression of maternal genes and transcriptional activation of zygotic genes, how epigenetic factors regulate developmental block is still unclear. In this study, we systematically analyzed whole-genome methylation levels during five stages of sheep oocyte and preimplantation embryo development using single-cell level whole genome bisulphite sequencing (SC-WGBS) technology. Then, we examined several million CpG sites in individual cells at each evaluated developmental stage to identify the methylation changes that take place during the development of sheep preimplantation embryos. Our results showed that two strong waves of methylation changes occurred, namely, demethylation at the 8-cell to 16-cell stage and methylation at the 16-cell to 32-cell stage. Analysis of DNA methylation patterns in different functional regions revealed a stable hypermethylation status in 3'UTRs and gene bodies; however, significant differences were observed in intergenic and promoter regions at different developmental stages. Changes in methylation at different stages of preimplantation embryo development were also compared to investigate the molecular mechanisms involved in sheep embryo development at the methylation level. In conclusion, we report a detailed analysis of the DNA methylation dynamics during the development of sheep preimplantation embryos. Our results provide an explanation for the complex regulatory mechanisms underlying the embryo developmental block based on changes in DNA methylation levels.